THE DISTINCTIVE FEATURES OF EILEEN CHANG’S WORKS - Tajimuratova Ilmira (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines the literary works of Eileen Chang, focusing on the uniqueness of her artistic style, the originality of her characters, and the thematic depth of her writings. Using a qualitative literary analysis approach, the study applies close reading alongside feminist and psychological perspectives to selected works such as Love in a Fallen City and The Golden Cangue. The research highlights Chang’s ability to portray complex human emotions and urban life through refined narrative techniques and rich imagery. It also explores her contribution to modern Chinese literature, particularly in comparison with Lu Xun. The findings demonstrate that her works combine aesthetic sophistication with deep insight into human nature, securing her place as one of the most significant writers of the 20th century.